Материальное положение, класс, раса. Частная собственность как фактор, регулирующий современные социальные дифференциации - Łopińska, Aleksandra (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The aim of the study is to evaluate the private property as a factor regulating modern social differences. Proving the proposed hypothesis the author focus on the financial state, position and class as a forms of social differences in the context of the civil law system.
Financial state, position, class. Private property as a factor regulating modern social differences
Keywords: private property; social differentiations; civil law